Clinical Outcome Differences in Mucinous Versus Non-Mucinous Colonic Adenocarcinoma: A Comparative Study - Adrian Cote; Roxana Loriana Negrut; Hany Abdulateif Salem; Bogdan Feder; Mircea Gheorghe Pop; Adrian Marius Maghiar (Diagnostics)
Background/Objectives: Colon cancer is one of the main causes of cancer-related mortality worldwide. Among its histopathological subtypes, mucinous adenocarcinoma (MAC) is characterized by a more aggressive behavior than non-mucinous adenocarcinoma (non-MAC). This study aimed to compare the clinical outcomes and postoperative recovery between MAC and non-MAC cases in order to better understand the treatment implications and optimize therapeutic strategies. Methods: A retrospective cohort study was conducted on patients diagnosed and treated at the Bihor County Emergency Hospital between January 2019 and December 2022. Data were collected from the medical records. Patients were divided into two groups, based on the histopathological results: mucinous adenocarcinoma and non-mucinous adenocarcinoma. Statistical analysis included descriptive statistics, t-tests, Chi-square tests, and ANOVA where appropriate. Results: A total of 191 patients were enrolled in this study, grouped in 36 cases of MAC and 155 cases of non-MAC. No significant statistical differences were found regarding hematological parameters. However, MAC was associated with higher rates of local invasion and a predominant right-sided colonic location, necessitating more frequent right colectomies. The overall mortality rate was significantly higher for MAC, indicating its aggressive nature. Conclusions: MAC presents higher local invasion rates and overall mortality. The aggressiveness of MAC underscores the need for tailored treatment approaches to optimize patient outcomes. Future large-scale studies are recommended to validate these findings and refine the therapeutic strategies.